2009
DOI: 10.1038/eye.2009.15
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between GDx VCC and Stratus OCT in juvenile glaucoma

Abstract: Purpose To compare the ability of scanning laser polarimetry (GDx VCC) and optical coherence tomography (OCT) to discriminate eyes with juvenile glaucoma from normal eyes and to assess the relationship between their parameters. Methods A total of 24 glaucomatous eyes of 24 patients and 24 normal eyes were enrolled. The age range of the patient was 11-40 years with a mean age of 25.1 ± 8.2 years. Contol groups consisted 24 eyes of 24 individuals without glaucoma with a mean age of 33.2 ± 8.2 years. All subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
2
6
0
Order By: Relevance
“…The glaucoma identifying capacity of pRNFL thickness measurements is well documented in adults [34,35] and has also been reported in children [12,13]. The present results corroborate the previous findings where a strong correlation was found between pRNFL thickness and the presence of glaucoma.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The glaucoma identifying capacity of pRNFL thickness measurements is well documented in adults [34,35] and has also been reported in children [12,13]. The present results corroborate the previous findings where a strong correlation was found between pRNFL thickness and the presence of glaucoma.…”
Section: Discussionsupporting
confidence: 92%
“…In children with glaucoma, a correlation between the thinning of the pRNFL and pathologic ONH cupping was previously shown [8,11]. Moreover, reports of a correlation between pRNFL thickness and the presence of glaucoma advocate for the potential diagnostic value of OCT for paediatric glaucoma [12,13].…”
Section: Introductionmentioning
confidence: 92%
“…[17][18][19][20][21][22][23][24][25] GDx VCC and Stratus OCT are reported to have similar diagnostic performance with respect to discrimination between healthy and glaucomatous eyes. [7][8][9][10][11] Recently, OCT technology has evolved from TD OCT (Stratus) to the SD OCT. SD OCT has a theoretical advantage over conventional TD OCT because of enhanced axial resolution and faster scan speed, and may thus provide higher quality images and more accurate measurements. 26 Recent publications have shown that the Cirrus OCT used in our current study has good measurement reproducibility.…”
Section: Discussionmentioning
confidence: 99%
“…This technology has higher axial resolution and scan speeds than the conventional TD Stratus OCT. 6 Several comparative studies have shown that GDx VCC and TD Stratus OCT are highly effective and have similar capabilities in the diagnosis of glaucoma. [7][8][9][10][11] However, to the best of our knowledge, no study has yet compared the glaucoma diagnostic capability of GDx VCC with that of the newly introduced SD Cirrus OCT in the same subjects. In the present study, we compared the diagnostic capability of these two devices in the same study population using similar inclusion and exclusion criteria.…”
Section: Introductionmentioning
confidence: 93%
“…Zareii[ 43 ] compared the ability of GDx-VCC and OCT to discriminate eyes with Juvenile Open-Angle Glaucoma from normal eyes. They observed statistically significant correlations between the two.…”
Section: Juvenile Open-angle Glaucomamentioning
confidence: 99%